Analisis Kausalitas Inflasi, Ketimpangan Pendapatan, Dan Pertumbuhan Ekonomi Di Indonesia - Muhamad Reza; Fajar Wahyu Dewanto; Bima Aris Waskito; Gebriel Musroni; Harjona Simanullang; Andika Pratama; Berdin Rumahorbo; Dicky Perwira Ompusunggu; Basunjaya, Buyung Libna (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to analyze the causal relationship between inflation, income inequality, and economic growth in Indonesia using the Vector Error Correction Model (VECM) and Granger Causality Test. The data analyzed covers the period from 1998 to 2023. The results show that inflation has a significant long-term impact on income inequality, with a coefficient of 3.640 and a t-statistic of 4.536. In contrast, economic growth does not exhibit a significant short-term causal relationship with income inequality, as indicated by an F-statistic probability of 0.2331. The Impulse Response Function (IRF) analysis reveals that shocks to inflation negatively affect income inequality, although the effect is temporary. The Variance Decomposition results indicate that, in the long term, inflation contributes 15.4% to the variability of income inequality, while the contribution of economic growth remains low. This study highlights the importance of inflation control to reduce income inequality and promote more inclusive and equitable economic growth.